2011
DOI: 10.1130/b30382.1
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary environmental reconstructions of playa-lunette system evolution on the central High Plains of Kansas, United States

Abstract: Playas are small, ephemeral wetlands found throughout semiarid and arid regions around the world. Lunettes are dunes that form downwind of some large playas. Two playa-lunette systems on the High Plains were investigated to reconstruct paleoenvironments during playa-lunette system evolution. Both playa-lunette systems are composed of sediment spanning >40 k.y., with earliest deposits accumulating during at least marine isotope stage (MIS) 3, and possibly starting as early as MIS 5. The Gilman Canyon Formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 73 publications
2
10
0
Order By: Relevance
“…According to this interpretation, a smooth solid floor, whose subsurface is probably saturated in liquids, would have been exposed at that time over the southern half of Ontario Lacus (Unit B, Figure 2). Based on this observation and on other geomorphological considerations, Cornet et al [2012] suggested that the closest Earth analogs for the Ontario Lacus landsystem are evaporitic ephemeral lakes that form in shallow flat‐floored karstic depressions under semi‐arid climates, such as the southern African pans or the Kansas playas [ Goudie and Wells , 1995; Miller et al , 2010; Bowen and Johnson , 2012]. This interpretation is consistent with previous suggestions that ephemeral lakes such as the Racetrack and Bonnie Claire Playas (Death Valley National Park, California) are relevant terrestrial analogues for Ontario Lacus [ Lorenz et al , 2010].…”
Section: Introductionsupporting
confidence: 78%
“…According to this interpretation, a smooth solid floor, whose subsurface is probably saturated in liquids, would have been exposed at that time over the southern half of Ontario Lacus (Unit B, Figure 2). Based on this observation and on other geomorphological considerations, Cornet et al [2012] suggested that the closest Earth analogs for the Ontario Lacus landsystem are evaporitic ephemeral lakes that form in shallow flat‐floored karstic depressions under semi‐arid climates, such as the southern African pans or the Kansas playas [ Goudie and Wells , 1995; Miller et al , 2010; Bowen and Johnson , 2012]. This interpretation is consistent with previous suggestions that ephemeral lakes such as the Racetrack and Bonnie Claire Playas (Death Valley National Park, California) are relevant terrestrial analogues for Ontario Lacus [ Lorenz et al , 2010].…”
Section: Introductionsupporting
confidence: 78%
“…Based on a compilation of data across the North American midcontinent, Williams et al (2010) note that continental drying occurred from 14 ka to 6 ka with a peak from 10 ka to 8 ka, but noted a spatial pattern to the drying with peripheral regions drying later. Many other studies suggest aeolian deposition and/or drier climates during this time period with a peak at around 6.5 ka to 4.5 ka (e.g., Holliday, 1989a;Dorale et al, 1992;Holliday, 1995;Johnson and Willey, 2000;Holliday, 2001;Asmeron et al, 2007;Forman et al, 2008;Bowen and Johnson, 2012;Briles et al, 2012;Halfen and Johnson, 2013;Buzas-Stephens et al, 2014).…”
Section: Environmental Reconstructionmentioning
confidence: 83%
“…Playas are ephemeral or desiccated lakes found throughout arid and semi‐arid regions of the world (Goudie and Wells, ; Yechieli and Wood, ; Shaw and Bryant, ; Goudie, ). In North America, they have been described in the Northern (Last and Schweyen, ), Central (Bowen and Johnson, , ; Bowen et al ., ) and Southern Great Plains (Wood et al ., ; Gustavson et al, ; Holliday, ; Holliday et al ., ), arid basins of the southern Pacific Coast Ranges (Eghbal et al ., ), the Mexican Plateau (Alcocer and Escobar, ) and throughout the Basin and Range region (Currey, ; Scuderi et al ., ). Due to their ephemeral nature playas are highly sensitive to climatic fluctuations and are influenced, often simultaneously, by fluvial, lacustrine and eolian processes (Holliday, ; Holliday et al ., ; Bowen and Johnson, , ; Rich, ), making them useful paleoenvironmental archives.…”
Section: Introductionmentioning
confidence: 99%